7(-2x+1)=-13x+1

Simple and best practice solution for 7(-2x+1)=-13x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(-2x+1)=-13x+1 equation:


Simplifying
7(-2x + 1) = -13x + 1

Reorder the terms:
7(1 + -2x) = -13x + 1
(1 * 7 + -2x * 7) = -13x + 1
(7 + -14x) = -13x + 1

Reorder the terms:
7 + -14x = 1 + -13x

Solving
7 + -14x = 1 + -13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13x' to each side of the equation.
7 + -14x + 13x = 1 + -13x + 13x

Combine like terms: -14x + 13x = -1x
7 + -1x = 1 + -13x + 13x

Combine like terms: -13x + 13x = 0
7 + -1x = 1 + 0
7 + -1x = 1

Add '-7' to each side of the equation.
7 + -7 + -1x = 1 + -7

Combine like terms: 7 + -7 = 0
0 + -1x = 1 + -7
-1x = 1 + -7

Combine like terms: 1 + -7 = -6
-1x = -6

Divide each side by '-1'.
x = 6

Simplifying
x = 6

See similar equations:

| 66=6(g+2) | | -4-5x+2=-21x+7-5x | | 7x-53x+12= | | 3j+10=67 | | xtan(0.5x)=2 | | 2(x)+22=4(x+3) | | 3w^3-18w^2+15w=0 | | 4/(4x^2-x-24)=7/(7c^2-7c-36) | | 3(3x-6)=6(4x-8)-5x | | 1/2y−8=−10 | | 2x-5+2(3x)+13=-2-2x+(16-5) | | (9b-6)-4(2b+2)=-7 | | 100=34 | | 5-4x=11x | | 5-(6-3n)=2 | | G(x)=x^2+3x-54 | | 12x/4=-2y/2 | | G(x)=x^2+9x+20 | | 2=x/-5 | | 9b-9b=11(b-7)+8(b+12) | | 2y^2+18y+80=0 | | -4/7en-3/7en= | | -8=1x+-12-10 | | (3x-4)(7x+4)=0 | | x^2=36-5x | | 4x-5+2(3x)+17=-2-3x+(9-5) | | 13-x=-1 | | -4/7en--3/7en= | | Y=27x+10.50 | | 4(3y-1)=-40 | | 7x-2(x-4)= | | 10x+5+8=12x-3x+80 |

Equations solver categories